Cultural-beliefs’ influence on students’ learning of livestock production in Ogun State, Nigeria - Adesanya, Emmanuel Olorunleke; Ojo, Afolabi Kayode Ojo; Bature, Shuaib Suleiman; Bolakale, Jimoh Saidu Bolakale (Universitas Negeri Semarang, 2024)
The culture of students often influences how agricultural topics are learned. This study examined the impact of cultural beliefs senior secondary school agriculture students held on their livestock production learning in Ogun State, Nigeria. The study employed a survey research design guided by four research objectives. The population consisted of all senior secondary school agriculture students in Ogun State, and a multi-stage sampling technique was used to select participants. Data were collected using a researcher-designed questionnaire and analysed using mean and standard deviation. The findings revealed that parents, peers, and traditional religious leaders are the primary sources of students’ cultural beliefs. These beliefs, often expressed as taboos, rituals, and superstitions, significantly influence students’ learning of livestock production. To address this, sensitising teachers about the interaction between cultural beliefs and the teaching of scientific principles is recommended.